Reservoir characterization of the Mesozoic successions in the Loppa High and the Hammerfest Basin, Norwegian Barents Sea - Kizatbay, Alseit (2021)
The study focuses on reservoir characterization of the Triassic, Jurassic, and Cretaceous successions In the Loppa High and the Hammerfest Basin, Norwegian Barents Sea. Characterization of reservoirs is based on petrophysical analysis, rock physics diagnostics, and AVO modelling. Well log data from seven exploration wells 7222/11-1 (Caurus), 7222/11- 2 (Langlitinden), 7122/2-1, 7122/6-1 (Tornerose), 7122/4-1, 7121/1-1 and 7120/2-2 are utilized. The potential sandstone reservoirs are Kobbe, Snadd, and Fruholmen Formations of Triassic age; Tubåen, Nordmela, and Stø Formation of Jurassic age and Knurr Formation of Cretaceous age. Kobbe and Snadd Formations comprise the main hydrocarbon reservoirs with the highest proven hydrocarbons in the study area. Therefore, this study has given particular focus on these two formations. Reservoir properties (e.g. porosity, permeability, shale volume, water saturation and net-togross ratio) are calculated for the seven formations utilizing petrophysical analysis techniques. Potential reservoir and pay zones are identified based on cutoff values (net reservoir: porosity≥0.06 and shale volume≤0.5; net pay: water saturation≤0.6). Rock physics diagnostics is performed by correlating elastic properties with the results obtained from the petrophysical analysis and crossplotting the data using rock physics templates. Furthermore, cement volume is estimated, and sensitivity of fluid saturation and lithology variations are evaluated. In addition, fluid sensitivity and lithology variations are also investigated using AVO modelling on selected reservoir units. The main reservoirs of Kobbe, Snadd, and Knurr Formations have been modelled and differentiated based on AVO classifications. The shallowest reservoir unit is the Cretaceous Knurr Formation which yields good reservoir properties. However, the formation is not rich in hydrocarbons. The Jurassic reservoir sandstones of Tubåen, Nordmela and Stø Formations, yield the best reservoir properties. Unfortunately, all three formations are dry in the studied wells. The Triassic sandstones of Kobbe, Snadd and Fruholmen Formations, show poorer reservoir quality compared to Jurassic and Cretaceous successions. Fruholmen Formation has better average reservoir properties compared to Snadd and Kobbe Formations. However, Snadd and Kobbe Formations are more abundant in hydrocarbons (e.g., Caurus, Langlitinden, and Tornerose discoveries) and have several pay zones. Based on published shale compaction trends, uplift has been estimated to be between 1046 and 1596 meters in the study area. Quartz cement is present in all formations, and as expected, the average cement volume increases from shallower formations to deeper formations. Rock physics crossplots such as Vp versus Vs, Vp/Vs versus AI, and LMR prove high sensitivity to fluids. Vp versus Vs, density versus Vp and Vp/Vs versus AI crossplots also proved to be good to discriminate lithology. The AVO modelling results demonstrate a clear separation between hydrocarbon and brine saturated reservoirs. In general, AVO modellings show high sensitivity to water saturation, porosity, shale volume wavelet, and block size. The reservoir of Knurr Formation from well 7120/2 2 produced Class I AVO signature. Reservoirs of Kobbe and Snadd Formations from well 7222/11-1 (Caurus) show Class III AVO signature. Reservoirs of Knurr Formation from well 7122/6-1 (Tornerose) and Snadd Formation from well 7222/11-2 show Class IV AVO signature. This study integrated only well log data and information from previous studies. Core analysis and seismic data can be integrated in future studies to support the results produced from well log data and enhance the understanding of potential prospectively in the study area.